EOCENE DIATOMS AND SILICOFLAGELLATES FROM THE KRONOTSKII BAY DEPOSITS (EAST KAMCHATKA) - Tsoy I.B. (My University, 2003)
Eocene diatoms and silicoflagellates from deposits of the Kronotskii Bay are the oldest known fossils of siliceous phytoplankton from the northwestern Pacific. More than 130 species of 59 diatom genera and 24 species of 5 silicoflagellate genera are identified. Three diatom assemblages of middle Eocene age (those of Lisitzinia kanayai, Lisitzinia inconspicua var. triloba, and Praecymatosira monomembranaceae zones) and one presumably corresponding in age to the middle-late Eocene (diatoms of Rylandsia conniventa Zone) are established. A diverse silicoflagellate assemblage described for the first time characterizes the Dictyocha hexacantha Zone. All the assemblages are supposed to have been formed mainly in bathyal environments and under a relatively high (almost subtropical) temperature of surface water.
Keywords: diatoms; silicoﬂagellates; middle Eocene; Kronotskii Bay; East Kamchatka; paleoenvironment; northwestern Paciﬁc; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен